Design, synthesis, in vitro characterization and preliminary imaging studies on fluorinated bile acid derivatives as PET tracers to study hepatic transporters. Issue 3 (1st February 2017) - Testa, Andrea; Dall'Angelo, Sergio; Mingarelli, Marco; Augello, Andrea; Schweiger, Lutz; Welch, Andy; Elmore, Charles S.; Sharma, Pradeep; Zanda, Matteo
Graphical abstract: Abstract: With the aim of identifying a fluorinated bile acid derivative that could be used as [ 18 F]-labeled Positron Emission Tomography (PET) tracer for imaging the in vivo functioning of liver transporter proteins, and particularly of OATP1B1, three fluorinated bile acid triazole derivatives of cholic, deoxycholic and lithocholic acid (CATD, DCATD and LCATD4a –c, respectively) were synthesized and labeled with tritium. In vitro transport properties were studied with cell-based assays to identify the best substrate for OATP1B1. In addition, the lead compound, LCATD (4c ), was tested as a substrate of other liver uptake transporters OATP1B3, NTCP and efflux transporter BSEP to evaluate its specificity of liver transport. The results suggest that4c is a good substrate of OATP1B1 and NTCP, whereas it is a poor substrate of OATP1B3. The efflux transporter BSEP also appears to be involved in the excretion of4c from hepatocytes. The automated radiosynthesis of [ 18 F]-4c was accomplished in a multi-GBq scale and a pilot imaging experiment in a wild type rat was performed after i.v. administration to assess the biodistribution and clearance of the tracer. PET imaging revealed that radioactivity was primarily located in the liver (tmax = 75 s) and cleared exclusively through the bile, thus allowing to image the hepatobiliary excretion of bile acids in the animal model. These findings suggest that [ 18 F]-LCATD4c is a promising PET probe for the evaluation of hepatic transporters OATP1B1, NTCP and BSEP activity with potential for studying drug-drug interactions and drug-induced toxicity involving these transporters.